Pengaruh Model Pembelajaran Problem Based Learning (PBL) terhadap Kemampuan Berpikir Kritis dan Pemecahan Masalah pada Mata Pelajaran Administrasi Umum Kelas X OTKP di SMK Negeri 10 Surabaya - Nurul Yuli Rachmawati; Brillian Rosy (Universitas Negeri Surabaya, 2020)
This study aims to see the influence of problem-based learning model (PBL) for critical thinking and problem solving skills in the general implementation of X-OTKP class in SMK Negeri 10 Surabaya. The type of research used is quasi Experimental Design Research, with the design of non-equivalent Control Group Design Research. The research samples use class X OTKP 1 and X OTKP 2 with a Total of 36 students. Data collection techniques in the form of interviews, observations, tests, and documentation. Research instruments used test sheets (pretests and posttests) as indicators of critical thinking ability, and a skill sheet used as an indicator of problem-solving capabilities. Analysis of research data using independent sample test test and gain score.Based on the results of analysis of T tests for problems Pretest and Posttest obtained tcount 3.611 with significance level 0.001. With a confidence level of 95%, the value of Î± = 0.05, with (df) 70 so that it is obtained with (1.997). The results of the troubleshooting analysis obtained tcount 3.562 with a significance of 0.000 with a 95% confidence rate, value of Î± = 0.05, with (df) of 70 so obtained this by (1.997). The gain score is tcount 2.065> ttable 1.997 then can be deduced H0 rejected then H1 received. The Inconclusive Learning Model (PBL) affects critical thinking ability and problem solving skills in the general administration of X-OTKP class in SMK Negeri 10 Surabaya.